ADMINISTRATIVE AND SOCIAL DETERMINANTS OF STUDENTS’ SPORTS PARTICIPATION IN SECONDARY SCHOOLS IN KWARA STATE, NIGERIA (2014)
Participation in sports is of immense benefit to the soundness of an individual mental and social wellness, particularly youngsters. Recently there has been great involvement of youngsters in school games arising from the high administrative supports and social values attached to sports. Previous studies on documentation youngsters’ participation in sports had focused more on other factors (such as demographic and personal) rather than administrative and social. This study, therefore, investigated the importance of administrative (facilities, equipment, funding, schedulling, administrative style and personnel) and social (peer influence, parental influence, gender, religious beliefs and cultural beliefs) factors on students’ sports participation in private and public secondary schools in Kwara State, Nigeria. The descriptive survey research design was adopted. The stratified random sampling technique was used to select 2,560 students and 64 teachers from public (16) and private (16) secondary schools. Five instruments were used: Administrative Determinant Questionnaire for Students (r=0.82) Social Determinant Questionnaire for Students (r=0.76), Administrative Determinant Questionnaire for Teachers (r=0.73), Social Determinant Questionnaire for Teachers (r=0.76), and Students’ Sport Participation Questionnaire (r=0.73). Four research questions were answered and six hypotheses tested at 0.05 level of significance. Data were analysed using Pearson’s product moment correlation and multiple regression. Administrative and social factors significantly determined participation in sports for students (F (6, 2553) = 968.15) and for teachers (F (6, 57) = 31.06). These contributed 69.0% and 71.0% to the variance of sports participation respectively. The relative contributions of administrative factors among the students were: schedulling (β=0.447), equipment (β=0.444), facilities (β=0.314), funding (β=0.301), personnel (β=0.27) and administrative style (β=0.059). Relatively, also the social factors contributions among the students were: peer influence (β=0.058), parental influence (β=0.076), religious beliefs (β=0.094) and cultural beliefs (β=0.065). Gender was not significant. The relative contributions of independent variables among the teachers: administrative factors (equipment (β=0.648), facilities (β=0.528), schedulling (β=0.299), funding (β=0.244)) and social factors (peer influence (β=0.222), parental influence (β=0.166), gender (β=1.76) and cultural beliefs (β=0.172)) However, administrative style, qualified personnel and religious beliefs were not significant. Sport participation had significant relationships with the independent variables as follows: equipment (r=-.584), schedulling (r=-.407), funding (r=-.348), peer influence (r=-.332), gender (r=-.249), cultural beliefs (r=-.245), religious beliefs (r=-.184), personnel (r=-.139), facilities (r=-.119), administrative style (r=-.112) and parental influence (r=-.030). Significant difference existed between students’ sports participation in public ( =33.16) and private ( =32.47) secondary schools. Schedulling, equipment, facility and funding are the most potent factors that determined sports participation in private and public secondary schools. Therefore, sports equipment and facilities should be made more available and well managed to promote sports participation among secondary school students. Besides, more sports personnel who are administratively qualified should be recruited while more peer interactions are encouraged among the students.